TTFs nonsymmetrically fused with alkylthiophenic moieties - Silva, Rafaela A. L.; Vieira, Bruno J. C.; Andrade, Marta M.; Santos, Isabel C.; Rabaça, Sandra; Belo, Dulce; Almeida, Manuel (Beilstein Journal of Organic Chemistry, 2015)
Two new dithiolene ligand precursors, containing fused TTF and alkyl thiophenic moieties 3,3'-{[2-(5-(tert-butyl)thieno[2,3-d][1,3]dithiol-2-ylidene)-1,3-dithiole-4,5-diyl]bis[sulfanediyl]}dipropanenitrile (α-tbtdt, 1), and 3,3'-{[2-(5-methylthieno[2,3-d][1,3]dithiol-2-ylidene)-1,3-dithiole-4,5-diyl]bis[sulfanediyl]}dipropanenitrile (α-mtdt, 2), were synthesized and characterized. The electrochemical properties of these electronic donors were studied by cyclic voltammetry (CV) in dichloromethane. Both compounds show two quasi-reversible oxidation processes, versus Ag/AgCl, typical of TTF donors at E11/2 = 279 V and E21/2 = 680 V for 1 and E11/2 = 304 V and E21/2 = 716 V in the case of 2. The single-crystal X-ray structure of 1 and of a charge transfer salt of 2, (α-mtdt)[Au(mnt)2] (3), are reported.
Keywords: cyclic voltammetry; single-crystal X-ray diffraction; supramolecular chemistry; tetrathiafulvalene (TTF); thiophene